Internalisasi Nilai-Nilai Moderasi Beragama dalam Pembelajaran Al-Qur’an – Hadist di Pesantren - Hadiyanto, Andy; Rohma Kubro; Samitri, Cendra (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2023)
Islamic educational institutions, especially Pesantren, as one of the components of education, have a vital role as a responsible forum in efforts to reduce the development of radicalism. Lessons in Pesantren, especially the study of the Quran and hadith, require a paradigm shift that can bring Islamic scholarship so that it is not rigid in dealing with issues of radicalism. The study of the Quran and hadith in Pesantren that seems normative and past-oriented must now emerge by internalising the values of religious moderation as a solution to dealing with existing spiritual problems. Training has been held at Nurul Huda Setu Islamic Boarding School Bekasi, West Java, to internalise the values of religious moderation for teachers and educators as facilitators of understanding religious moderation through learning the Quran and hadith. This training is divided into two sessions, namely a theory session and a practical session. Theory sessions use lectures, discussions, and question-and-answer methods. At the same time, practical sessions are carried out through workshops. This training introduced iceberg analysis (iceberg analysis) and U process (U process) developed by Senge and Hamilton. The series includes event analysis, pattern of behavior analysis, and finally system structure examine. The series results can be followed up with the U process, which allows rethinking, redesigning, reframing and reacting.